Ginseng polysaccharides enhanced ginsenoside Rb1 and microbial metabolites exposure through enhancing intestinal absorption and affecting gut microbial metabolism - Shen, Hong; Gao, Xue-Jiao; Li, Ting; Jing, Wang-Hui; Han, Bei-Lei; Jia, Yu-Meng; Hu, Nan; Yan, Zhi-Xiang; Li, Song-Lin; Yan, Ru (Journal of ethnopharmacology, 2018)
Polysaccharides and small molecules commonly co-exist in decoctions of traditional Chinese medicines (TCMs). Our previous study outlined that ginseng polysaccharides (GP) could interact with co-existing ginsenosides to produce synergistic effect in an over-fatigue and acute cold stress model via gut microbiota involved mechanisms. This study aimed to verify the interactions by examining the impact of GP on oral pharmacokinetics of ginsenoside Rb1 (Rb1), the dominant protopanoxadiol (PPD)-type ginsenoside in Ginseng, on a dextran sulphate sodium (DSS) induced experimental colitis model which was characterized by gut dysbiosis, and to delineate the underlying mechanisms in vitro. Rats received drinking water (normal group), 5% DSS (UC group), or 5% DSS plus daily oral administration of GP (GP group) for 7 days and fecal samples were collected on day −3, 0 and 6. On day 7 all animals received an oral dosage of Rb1 and blood samples were withdrawn for pharmacokinetic study. The in vitro metabolism study of Rb1 in gut microbiota from normal and UC rats and the transport study of Rb1 across Caco-2 cell monolayer were carried out in presence/absence of GP. Rb1 and its bacterial metabolites ginsenoside Rd (Rd), ginsenoside F2 (F2), Compound K (CK) and PPD were determined using LC-MS/MS. Total and target bacteria in fecal samples were determined by using 16S rRNA-based RT-PCR. β-Glucosidase activity was determined by measuring 4-nitrophenol formed from 4-nitrophenyl-β-D-glucopyranoside hydrolysis. DSS induction did not alter AUC0−t and Cmax of Rb1, which, however, were doubled together with elevated AUC0−t of the metabolites, in particular Rd and CK, in GP group. GP influenced the microbial composition and showed a prebiotic-like effect. Accordingly, GP treatment could partially restore the β-glucosidase activity which was reduced by DSS induction. The presence of GP resulted in quicker microbial metabolism of Rb1 and higher Rd formation in first 8 h of incubation, while the impact on F2 and CK formation/conversion became obvious after 8 h. More interestingly, GP slightly stimulated Caco-2 cell growth and facilitated Rb1 transport across the Caco-2 monolayer in both directions, increasing the Papp of Rb1 from 10−7 cm/s to 10−6 cm/s. Conclusions: GP alleviated DSS-induced colitis-like symptoms and enhanced the systemic exposure of Rb1 through enhancing microbial deglycosylation and intestinal epithelial absorption of Rb1. These findings further demonstrated the important role of gut microbiota in the multifaceted action of polysaccharides in the holistic actions of traditional decoction of TCMs. [Display omitted]